Sex differences in FSH‐regulatory peptides in pubertal age boys and girls and effects of sex steroid treatment - Foster, Carol M.; Olton, Pamela R.; Racine, Michael S.; Phillips, David J.; Padmanabhan, Vasantha (Human reproduction (Oxford), 2004)
BACKGROUND: FSH concentrations are higher in girls than in boys before puberty. We hypothesized that steroid‐mediated changes in FSH‐regulatory proteins underlie the sex differences in FSH secretion and pubertal timing. METHODS: FSH‐regulatory proteins, LH, FSH and sex steroids were measured in five boys, 10 girls, and five girls with Turner syndrome before and during sex steroid treatment (girls, 0.05 mg/day estradiol; boys, 5 mg/day testosterone) for up to 4 weeks. Blood was obtained every 15 min from 20.00 to 08.00 h before and during sex steroid treatment. RESULTS: The mean FSH concentration was higher in girls than in boys (P = 0.0044). Activin‐A concentrations were greater (P < 0.0001) and inhibin‐B concentrations lower (P < 0.0001) in girls compared with boys. Steroid treatment (i) suppressed LH/FSH concentrations in all subjects; (ii) increased the mean activin‐A concentration in all but the Turner girls (P = 0.001); and (iii) decreased inhibin‐B concentrations in boys (P = 0.005) but not in girls. Total follistatin and follistatin 288 concentrations did not differ by sex. CONCLUSIONS: Sex steroids regulate circulating activin‐A and inhibin‐B concentrations in children. The lower inhibin‐B and higher activin‐A concentrations may explain the higher FSH and earlier onset of puberty in girls.